Ejercicios Isométricos para el Tratamiento del dolor Cervical puro del adulto. GAD Provincial Chimborazo, 2018 - Galarza Sañay, Fausto Santiago (2019)
Back pain, especially in the cervical spine has reached a high percentage in recent decades, specifically in the administrative staff on the Provincial GAD of Chimborazo in ages ranging from 25 to 55 years, it was shown that from 77 patients, 64% are women, it means that women suffer from pure cervical pain more than men due to the same fact that the female sex works more on a desk in front of a computer, for this reason the isometric exercises were used as a treatment for demonstrating the effectiveness that can be obtained by alleviating and reducing pain in the 2018 period. This study had as its primary basis an initial and final evaluation of the administrative staff, using the modified Clinical History, which obtained qualitative and quantitative data since by means of the Visual Analogue Scale, (known in Spanish as EVA, or VAS in English), the O´donoghues test and the bell sign were able to measure and touch the type of muscle cervical pain; allowing a pre and post comparison applying the isometric exercises. The study also had a mixed approach, the level of investigation was applicative with a quasi-experimental design, it was a transversal research, it was on field since it allowed data collection, and it was documental since it was based on the collection of every kind of information, it also had an exploratory and descriptive scope. Obtaining also with the type of scientific inductive method performing its analysis and comparison of results. In this way it is concluded that the application of isometric exercises had a positive effect as a technique for prevention and physiotherapy treatment.